Hoodoo - Smith, Ronald L. (Ronald Lenard), 1959- (Houghton Mifflin Harcourt, 2015)
Living in 1930s Alabama, twelve-year-old Hoodoo Hatcher's family has always practiced folk magic, or "hoodoo," but Hoodoo himself can't seem to cast a spell. But when a stranger comes to town looking for a boy with Hoodoo's name, Hoodoo must learn to conjure quickly if he wants to save his town from the stranger's black magic.